2016
DOI: 10.1097/md.0000000000003178
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Medical and Nursing Students’ Willingness to Donate Organs

Abstract: Malaysia suffers from a chronic shortage of human organs for transplantation. Medical and nursing students (MaNS) are future health professionals and thus their attitude toward organ donation is vital for driving national donation rates. This study investigates MaNS’ willingness to donate organs upon death and the factors influencing their willingness. A cross-sectional design was used with a sample of 500 students (264 medical and 236 nursing) at the University of Malaya. A self-administrated questionnaire wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
1
20
0
4
Order By: Relevance
“…This corresponds and contradicts many studies from different parts of the world. Similar findings were observed in the studies carried out in Qatar, where willingness was 57.3%, 17 India, where willingness was 57.3%, 26 Malaysia, where willingness was 55.6%, 27 Turkey, where willingness was 51.3%, 25 Korea, where willingness was 49.8% 28 and China, where willingness was 49.3. 29 However, contradictory results were shown in studies conducted in South India, where willingness was 89% 4 and Turkey, where willingness was 72%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This corresponds and contradicts many studies from different parts of the world. Similar findings were observed in the studies carried out in Qatar, where willingness was 57.3%, 17 India, where willingness was 57.3%, 26 Malaysia, where willingness was 55.6%, 27 Turkey, where willingness was 51.3%, 25 Korea, where willingness was 49.8% 28 and China, where willingness was 49.3. 29 However, contradictory results were shown in studies conducted in South India, where willingness was 89% 4 and Turkey, where willingness was 72%.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, monthly income was not significant, which is consistent with a study in Malaysia. 27 However, monthly income was found to be positively or negatively associated with organ donation in studies done in Qatar, 17 South India, 4 and Pakistan. 34 Though, respondents' perceptions that their religion supports organ donation was highly significant with willingness for organ donation in the bivariate analysis, it was insignificant in final multivariate logistic regression.…”
Section: Discussionmentioning
confidence: 98%
“…8,13,21 However, one observational study among medical students in Malaysia reported that student's attitude and willingness to donate organs highly influenced by religion. 7 Another two studies showed that religion is one of the major factors for the students not to donate the organ. 22,23 Future care providers who strongly believe that organ donation is against his or her belief in the religion may have a direct impact on the organ donation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the future students can be informed advocates to the public about organ donation. 5,7 In general, in Ethiopia, most of the time peoples are not volunteering to donate the organ to the patients who are waiting for urgent organ transplantation. The deferent factors which determine the rate of organ donation should be studied qualitatively and quantitively.…”
Section: Introductionmentioning
confidence: 99%
“…The attitude of healthcare professionals, as thus also healthcare students, toward organ donation is considered one of the most important factors to influence donation rates 18 . Clearly, donation rates need to be increased and so investigations of healthcare professional attitudes are needed, including nursesthe most common healthcare professional affected by moral distress.…”
Section: Organ Donation and Transplantation Processmentioning
confidence: 99%